Short-Term Training of Family Medicine Teams on Cardiovascular Risk Assessment and Management - Effects on Practice and Outcomes - Štrbac, Savka; Pilipović-Broćeta, Nataša; Todorović, Nevena; Vujić-Aleksić, Vesna; Stević, Siniša; Lolić, Amela; Šeranić, Alen; Vulić, Duško; Bokonjić, Dubravko; Škrbić, Ranko (Scripta Medica, 2021)
Background/Aim: The prevention of cardiovascular risk factors and cardio- vascular disease management contributes to the cardiovascular mortality reduction. The effects of these activities have been measured by quality indicators. The aim of this study was to determine the effects of family medicine team training workshop and implementation of clinical guidelines on the cardiovascular risk factors and diseases management in primary health care in the Republic of Srpska/Bosnia and Herzegovina. Methods: The “CardioVascular Risk Assessment and Management” study included a sample of 373 teams from 41 primary health care centres trained to provide adequate services and to compare the quality of cardiovascular risk management before and after the training workshop and implementation of clinical guidelines. The comparison was based on nine project defined performance indicators related to hypertension, type 2 diabetes mellitus, hyperlipidaemia, tobacco smoking and obesity. Results: Significant improvements were observed in six indicators after the training workshop and implementation of guidelines. Target values for blood pressure and HbA1c were achieved in over 80 % of patients (82.12 ± 15.81 vs 84.49 ± 12.71 and 84.49 ± 12.71 vs 85.49 ± 24.55; before and after the training workshop, respectively), while the target values for LDL cholesterol were achieved in 54.98 % ± 20.33 before and 57.64 % ± 16.66 after the training workshop. The number of teams that had less than 20 % of recorded data significantly decreased after the training workshop and guidelines implementation, and adequate recording of all indicators was improved. Conclusion: The training workshop of family medicine teams and implementation of clinical guidelines resulted in significant quality improvement of cardio- vascular diseases management in primary health care.